توظيف الشخصية في القصيدة الجديدة/ حميد سعيد انوذجا (Journal Of Educational and Psychological Researches, 2016)
This poem is regarded an important Harmonized structure in modern and Contemporary Culture to achieve aqualitative poem Comported with the other cultural structures inorder to discover the ego and aspiration in shaping distinctive voices.The Iraqi poetry is affected tangibly by this poem because of the intellective vaccinating between Iraqi and Arab poets ingeneral and western cultures in particular as a result of the tranplahin movement and other important means.The modern poet wood to ask some important characters to enrich his technician text inspite the fact that this is not a new way in Arab poetry but it takes avarant – criented to become outside the limits of rigid description within ongoing kinematic structure to be in the dramatic structure of technrcranhe texts.The privacy of the poet ( Hameed Saeed ) lise between what is ego and who objected in this poetical experiences – Being affected by other poets reflected in the poetical contexts specifically in historical attitude most of those poets are religions hishrical or general characters classified within the strife line including those characters who have Rebellions expectation.